Genetic diversity in Sclerotium oryzae population of rice based on random amplified polymorphic DNA markers - B. L. JALALI, A. KUMAR, RAM SINGH*, K. S. BOORA (Indian Phytopathology, 2010)
Fifteen Indian isolates of rice stem rot fungus Sclerotium oryzae collected from major rice growing belt of Haryana were investigated by DNA fingerprinting. Twenty two RAPD primers resolved 251 bands across 15 isolates with a maximum resolution of 15 bands observed in nine primers. Highest similarity value was between isolates SO 14 and SO 15 collected from varieties HKR 126 and Pusa Basmati No. 1 grown at Kaithal and Sirsa areas. Maximum diversity was observed in isolate SO 2 from variety Govind followed by SO 9 from variety IR 64. Isolate SO 2 out grouped from rest of the isolates at 39 per cent dissimilarity and this isolate was from a region in Karnal having a higher cropping intensity due to cultivation of two rice crops (summer and Kharif crops) in a year.